2014
DOI: 10.3892/ijo.2014.2413
|View full text |Cite
|
Sign up to set email alerts
|

Loss of miR-100 enhances migration, invasion, epithelialmesenchymal transition and stemness properties in prostate cancer cells through targeting Argonaute 2

Abstract: Evidence in literature has demonstrated that some microRNAs (miRNAs) play a pivotal role in most solid tumor metastasis. Previous studies have showed that miR-100 is downregulated in human prostate cancer tissue compared to normal prostate and also significantly decreased in bone metastatic prostate cancer samples compared with primary prostate cancer. Argonaute 2 (AGO2) is the core effector protein of the miRNA-induced silencing complex and overexpression of AGO2 might enhance tumor metastasis. However, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 55 publications
3
44
0
1
Order By: Relevance
“…The expression of AGO2 is dysregulated in many types of cancer (13,15,38), and the dysregulation of AGO2 results in altered miRNA activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of AGO2 is dysregulated in many types of cancer (13,15,38), and the dysregulation of AGO2 results in altered miRNA activity.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of AGO2 is tightly regulated at both transcriptional and post-transcriptional levels (10). Dysregulation of AGO2 has been reported in many tumors, including lung cancer (11), prostate cancer (12,13), hepatocarcinoma (14), and melanoma (15), but the role of AGO2 and how its expression is regulated in cervical cancer have not been well studied.…”
mentioning
confidence: 99%
“…miRNAs regulate downstream target gene expression at a post-transcriptional level by binding with specific sequences in the 3'-untranslated region (3'-UTR) of downstream target genes, leading to mRNA degradation and/or translational inhibition (12). Several lines of evidence have indicated that aberrant expression of miRNAs is involved in the progression and metastasis of different types of cancer (13)(14)(15)(16)(17)(18). Furthermore, research has indicated that upregulation or downregulation of a certain miRNA (let-7a) was directly correlated with the response to chemotherapeutic agents (19).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these, the downregulation of miR-100 was also shown in hepatocellular carcinoma, oral cancer, and adrenocortical cancer (Henson et al, 2009;Doghman et al, 2010;Chen et al, 2013). In contrast, an upregulation of miR-100 has been observed in renal cell carcinoma, acute myeloid leukemia, and prostate cancer (Akbari Moqadam et al, 2013;Wang et al, 2013;Wang et al, 2014). Previously, Oliveira et al (2011) found that miR-100 acted as a tumor suppressor in human bladder carcinoma 5637 cells.…”
Section: Discussionmentioning
confidence: 99%